2010
DOI: 10.1111/j.1600-0706.2009.17649.x
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of nest predation in passerines depends on predator species and time scale

Abstract: It has been proposed that some specific locations of bird's nests have higher intrinsic chances of being depredated than other locations. This predicts that fates of consecutive nesting attempts at the same site should be repeatable. We used 20 pairs of old thrush nests to simulate repeated nesting attempts at the same sites, both within and between breeding seasons (n=40 sites×2 trials×2 years=160). Each nest was monitored by a camera to record multiple predation events and to identify predators. Predation by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 48 publications
0
24
1
Order By: Relevance
“…Whether nest predation is mostly incidental or learned is not yet clear (Vigallon and Marzluff 2005). Predation on artificial nests in the present study system was shown to be repeatable within experimental trial (*length of nesting cycle) for all major predators, which was explained by a short-term effect of predator memory, rather than by independent multiple discoveries of the same nest (for details, see Weidinger and Kočvara 2010). In line with this, several aspects of predator behaviour at real nests as described here (revisitation of partially depredated nests, post-predation visits, non-lethal visits to active nests) suggest that predators can memorise nest locations, thus making learned nest searching possible (Sonerud and Fjeld 1987).…”
Section: Implications For Interpretation Of Nest Predation Patternsmentioning
confidence: 70%
See 1 more Smart Citation
“…Whether nest predation is mostly incidental or learned is not yet clear (Vigallon and Marzluff 2005). Predation on artificial nests in the present study system was shown to be repeatable within experimental trial (*length of nesting cycle) for all major predators, which was explained by a short-term effect of predator memory, rather than by independent multiple discoveries of the same nest (for details, see Weidinger and Kočvara 2010). In line with this, several aspects of predator behaviour at real nests as described here (revisitation of partially depredated nests, post-predation visits, non-lethal visits to active nests) suggest that predators can memorise nest locations, thus making learned nest searching possible (Sonerud and Fjeld 1987).…”
Section: Implications For Interpretation Of Nest Predation Patternsmentioning
confidence: 70%
“…The low frequency of such behaviours found in this and similar studies of real nests represents a minimum estimate, as not all non-termination events could be safely detected. Only a few artificial nest studies have been designed to record multiple events per nest (Leimgruber et al 1994;Weidinger and Kočvara 2010), but those studies suggest that multiple predations by the same or by different predator species might be more common.…”
Section: Predator Behaviourmentioning
confidence: 99%
“…Thomson, unpublished data). In boreal forests, a large array of mesopredator species coexist and share similar prey, including passerine nests (Weidinger and Kobvara 2010). Therefore, passerine nest predation risk depends on the distribution of the entire mesopredator community in the area and on the interspeciWc interactions occurring among mesopredators.…”
Section: Discussionmentioning
confidence: 99%
“…First, small mustelids such as stoats (Mustela erminea) and least weasels (M. nivalis) that subsist mainly on Microtus and Myodes voles but shift to alternative prey, such as passerine nests, when vole density is low (Korpimäki et al 1991). Secondly, there are generalist nest predators, such as the great spotted woodpecker (Dendrocopos major), the European Jay (Garrulus glandarius), the pine marten (Martes martes) and the red squirrel (Sciurus vulgaris); all are common predators of passerine nests (Weidinger and Kobvara 2010).…”
Section: Study Systemmentioning
confidence: 99%
“…In addition, they can memorize the place of easily accessible food (clutch position) (e.g. Angelstam 1986, Sonerud & Fjeld 1987, Danielson et al 1997, Roos 2004) and thus they would arrive to the experimental clutches within a shorter time in the stage of feeding the nestlings if a previous predation attempt was successful (Willebrand & Marcström 1988, Weidinger & Kočvara 2010.…”
Section: Introductionmentioning
confidence: 99%